2022
DOI: 10.1021/acssuschemeng.2c00621
|View full text |Cite
|
Sign up to set email alerts
|

Photoenhanced Oxidase–Peroxidase-like NiCo2O4@MnO2 Nanozymes for Colorimetric Detection of Hydroquinone

Abstract: Artificial oxidase and peroxidase mimics that are based on nanomaterials have drawn enormous attention due to their high stability, high efficiency, and low cost as compared with natural enzymes. Achieving multifunction and further boosting catalytic efficiency are two key directions of future nanozyme development. In this work, NiCo2O4@MnO2 microcubes with p–n junctions were constructed, exhibiting both oxidase- and peroxidase-like activities, capable of catalyzing the oxidation of tetramethylbenzidine (TMB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…20 NiCo 2 O 4 has attracted much attention in the field of catalysis on account of its unique, bimetallic element synergistic effect, 21,22 controllable morphological properties, 23 tunable band gap, and good electron transfer properties compared to single oxides. 24 According to research reports, NiCo 2 O 4 with superior electrochemical performance has been rarely studied in the field of PEC immunosensor. Therefore, p-type NiCo 2 O 4 with a 300 nm core−shell structure has a large specific surface area and can expose more active sites, which also provides a guarantee for its use as a secondary antibody marker in the PEC biosensing platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 NiCo 2 O 4 has attracted much attention in the field of catalysis on account of its unique, bimetallic element synergistic effect, 21,22 controllable morphological properties, 23 tunable band gap, and good electron transfer properties compared to single oxides. 24 According to research reports, NiCo 2 O 4 with superior electrochemical performance has been rarely studied in the field of PEC immunosensor. Therefore, p-type NiCo 2 O 4 with a 300 nm core−shell structure has a large specific surface area and can expose more active sites, which also provides a guarantee for its use as a secondary antibody marker in the PEC biosensing platform.…”
Section: Introductionmentioning
confidence: 99%
“…NiCo 2 O 4 is a typical transition metal oxide with a spinel structure, which has the advantages of low cost, good conductivity, high content, and excellent stability . NiCo 2 O 4 has attracted much attention in the field of catalysis on account of its unique, bimetallic element synergistic effect, , controllable morphological properties, tunable band gap, and good electron transfer properties compared to single oxides . According to research reports, NiCo 2 O 4 with superior electrochemical performance has been rarely studied in the field of PEC immunosensor.…”
Section: Introductionmentioning
confidence: 99%
“…MnO 2 nanosheet, a type of transition metal oxide, has low toxicity and good biocompatibility, rich redox chemistry, and excellent catalytic and oxidase-like activity. Owing to its superior chemical and physi-cal properties, many researchers have combined MnO 2 nanosheets with chem/biosensing techniques for the determination of dopamine, 14 hydroquinone, 15 glutathione, 16 salmonella, 17 etc. More importantly, different from the reported peroxidase mimics for colorimetric sensing, MnO 2 nanosheets represent a label-free colorimetric probe that can oxidize the colorless 3,3′,5,5′-tetramethylbenzidine (TMB) into a blue product (oxTMB), which has a characteristic UV-vis spectrum absorbance at 652 nm, without the addition of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…31 Ma et al have reported photoinduced peroxidase-like activity of NiCo 2 O 4 @MnO 2 nanozymes. 32 Multi-functional core-shell NPs and nanorattles have been synthesized using various soft chemical synthesis routes. For example, Wang et al have reported the synthesis of MnCo 2 O 4 @MnCo 2 S 4 core-shell nanostructures using the hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%